2017
DOI: 10.1111/liv.13481
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant screening for liver fibrosis and steatosis in French type 2 diabetic patients using Fibroscan

Abstract: The prevalence of significant steatosis is very high and significant fibrosis affect 12.7% of the patients. Fibroscan is an effective procedure to screen for fibrosis and steatosis in diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 30 publications
9
81
1
Order By: Relevance
“…The present study provides the first evidence that an SGLT2 inhibitor can prevent progression of hepatic fibrosis in patients with type 2 diabetes and NAFLD who have pre‐existing significant liver fibrosis, defined as LSM >8.0 kPa . Measurement of LSM by transient elastography was reported to be an easy non‐invasive method for reliably estimating the severity of liver fibrosis in patients with type 2 diabetes and NAFLD . In addition, LSM was found to be an accurate and reproducible parameter for detecting advanced liver fibrosis in patients with NAFLD that was comparable with liver biopsy .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The present study provides the first evidence that an SGLT2 inhibitor can prevent progression of hepatic fibrosis in patients with type 2 diabetes and NAFLD who have pre‐existing significant liver fibrosis, defined as LSM >8.0 kPa . Measurement of LSM by transient elastography was reported to be an easy non‐invasive method for reliably estimating the severity of liver fibrosis in patients with type 2 diabetes and NAFLD . In addition, LSM was found to be an accurate and reproducible parameter for detecting advanced liver fibrosis in patients with NAFLD that was comparable with liver biopsy .…”
Section: Discussionsupporting
confidence: 60%
“…In the present study, baseline LSM showed a strong positive correlation with several laboratory markers and scoring systems for liver fibrosis, including type 4 collagen, FIB‐4 index, and NAFLD fibrosis score. LSM ≥8.0 kPa is used as the threshold for excessive stiffness, which indicates clinically important liver disease, based on a large‐scale study of the general population in France that showed this value was an accurate predictor of liver fibrosis on biopsy . Another large population‐based study (the Rotterdam study) showed that 5.6% of the participants had an LSM ≥8.0 kPa and that elevation of LSM was strongly associated with diabetes and hepatic steatosis .…”
Section: Discussioncontrasting
confidence: 49%
“…Among patients with diabetes in Hong Kong seen in a hospital setting (n = 1,770) with a median BMI of 26.6 kg/m 2 , 17.1% had LSM ≥9.6 kPa using the M probe, whereas patients requiring use of the XL probe (n = 114) had higher BMI, waist circumference, systolic blood pressure, and hemoglobin A1c and 27.2% had LSM ≥9.3 kPa . These findings differ from two community‐based studies of patients with T2DM, where the prevalence of significant fibrosis was lower . In a French community‐based diabetic population (n = 669), the proportion of patients with LSM ≥8 kPa, 9.6 kPa, and 13 kPa was 12.7%, 7.3%, and 2.1%, respectively .…”
Section: Discussionmentioning
confidence: 74%
“…The XL probe was used when the skin‐capsule depth was ≥2.5 cm. Although optimal liver stiffness cut‐off values in NAFLD remain under discussion, for the purposes of this study, we used cut‐off values of 8.2 kPa for clinically significant fibrosis, ≥9.5 kPa for advanced fibrosis, and >13 kPa to indicate cirrhosis; the same cut‐off value was used for both probes …”
Section: Methodsmentioning
confidence: 99%
“…Thus, the direct use of a more specific test seems more suited to this setting (Figure B). This screening strategy has been tested by systematically performing liver stiffness measurements using TE in consecutive type 2 diabetes patients seen at diabetes clinics in Hong Kong (n = 1918) and in France (n = 705) . As a result, 13 to 18% of patients had elevated liver stiffness and 50% of those who underwent a liver biopsy (94 and 47 respectively) had advanced fibrosis.…”
Section: Referral Pathways From Primary Healthcare/diabetes Clinics Tmentioning
confidence: 99%